PEMBERANTASAN BUTA AKSARA AL-QURAN ANAK JALANAN DI SIMPANG PASAR PAGI PEKANBARU - M Zainudin (LPPM Universitas Abdurrab, 2017)
Take care of street children has been carried out by the Goverment of Pekanbaru, but the results of research on policies to manage of street children still leaves the problems included of illiteracy (especially the Alquran). Finally the program launched by the Goverment of Pekanbaru about maghrib recite of Alquran the period 2012-2017 will not be enjoyed by the street children. Community service activities is done by holding a persuasive approach, which provides guidance and teaching of the Alquran alphabets that are basic characters. The subject are street children in the Simpang Pasar Pagi Pekanbaru within two months. The methods used is to provide intensive managing from the scientific basis of reading and writing the Alquran. The results are the basic abilities possessed by street children in the science of religion. As a result, theranquillity and peace of the community will be created.